Kesiapan Mahasiswa Prodi PGSD UNIRA Malang dalam Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 - Wuli Oktiningrum (Jurnal Multidisiplin Madani, 2022)
Distance learning is an option that the Indonesian government must choose when facing the covid-19 pandemic. This is done to reduce the risk of transmission of COVID-19. This decision certainly caused various polemics and unpreparedness, including students of the PGSD UNIRA Malang Study Program. Therefore, this study was designed to determine the readiness of PGSD UNIRA Malang students in distance learning. This research uses descriptive observational method, with the number of respondents is 150 students. The results of this study indicate that UNIRA Malang PGSD Study Program students are ready to carry out distance learning to reduce the transmission rate of COVID-19, although in practice there are several internal and external obstacles.